EFFECT OF KINESIO TAPE VERSUS ATHLETIC TAPE ON MYOELECTRIC ACTIVITY OF ANKLE MUSCLES IN PATIENTS WITH CHRONIC ANKLE SPRAIN (International Journal of Physiotherapy, 2018)
Background: Sprained ankle a common orthopedic injury. The standard treatment for ankle sprains remains nonoperative. Ankle taping was used to protect and prevent ligaments excessive strain. So, the current study aimed at investigating the effect of spa-care Kinesio tape versus standard white athletic tape on myoelectric activities (EMG) of ankle evertors (peroneus longus) and invertors (tibialis anterior) in a chronic ankle sprain.Methods: A convenient sample of 30 patients with a chronic ankle sprain (18 females and 12 males) were included in this study. Their mean age ±SD was 24 ±1.2 years. Their height was 175±4.8 cm among men & 163±5.2 cm for females, and weight was 85±5.2 kg for males & 74±5.5 kg for women. It was a within-group design in which the same participant experienced the two types of taping compared to no taping condition. Root mean square (RMS) was measured while participants were moving the isokinetic dynamometer at an angular velocity of 120°/sec using concentric contraction mode through full ankle range of motion. The EMG (RMS) of evertors and invertors was measured immediately after the three taping ways (no tape, Kinesio tape, and athletic tape) with a one-week interval between each taping.Results: Spa-care Kinesiotape significantly reduced evertors and invertors EMG (RMS) compared with no tape or athletic tape in patients with chronic ankle sprain. Mean± SD of the evertors was 0.7 (±0.1) for no tape and 0.58 (±0.2) for Kinesio tape. The P value was 0.000 for kinesio tape in evertors compared with no tape. Also, mean± SD of the invertors was 0.87 (±0.23) for no tape, and 0.54 (±0.1) for Kinesio tape and the P value was 0.001 for Kinesio tape in invertors compared with no tape.Conclusion: Spa-care Kinesio tape may be useful for reducing EMG activity of ankle muscles in a chronic ankle sprain.